Experimental Study On The Performance Of Vertical Axis Hydrokinetic Turbine In Realistic Stream Condition - Ng, Wei Quan (Universiti Sains Malaysia, 2018)
Research on hydrokinetic turbine is increasing due to the energy demand by human being is increases. A small-scale, 13cm diameter, Vertical Axis Hydrokinetic Turbine (VAHT) designed, fabricated and equipped with rotational speed measure device to investigate the aerodynamic behaviour of the VAHT in a laboratory setting to study the effect of parameter changes and fluid structures. Vertical Axis Hydrokinetic Turbine is a facility that extract energy from moving water stream to generate electricity. The VAHT able to perform a maximum rotational speed of 113.87RPM at flow speed of 0.45m/s with a force-start motion. In the second part of this work, the adjustable design of the laboratory turbine enables operations with different number of blades, 1, 2, 3 and 4 blades, and present pitch angles, 0° and ±2°. Investigation of the effect of pitching angle and number of blade to the instantaneous rotational speed of the turbine is done by experimental method. Results indicate that toe-out pitch angle increases the rotational speed of the VAHT and shorten the time required to reach maximum rotational speed. As expected, decreasing number of blades will reduce the self-starting ability and increase the oscillation amplitude. However, the overall rotational speed will increase. In the third part of this work, low self-starting characteristic of VAHT was been studied in qualitative and quantitative method. The flow pattern of the water flow toward the VAHT was observed by using dye injection flow visualization method. The flow after upstream blade produces a large scale of wake and affect the performance of the downstream blade. The torque behaviour among 360° azimuth angle of the turbine is investigated by setting up 1-blade turbine in the water channel. There is only a region of azimuth angle that produces positive and useful torque to the VAHT. Next, the rotational speed of VAHT from initial stationary state and continues until the final steady-rotational condition is recorded to study its self-starting trend. As tip speed ratio lower than 1, VAHT shows a struggling behaviour to rotate in this critical region. Once the positive torque exceed negative torque, then VAHT able to rotate to its maximum Tip Speed Ratio.